Pengaruh Pendapatan Dan Pendidikan Terhadap Konsumsi Rumah Tangga Miskin Di Nagari Panti Timur Kecamatan Panti Kabupaten Pasaman - Deni Pratama Saputra; Yuwarman Mansur (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of income and education on the consumption of poor households in Nagari Panti Timur. The study used a quantitative approach with multiple linear regression analysis. Data were obtained through distributing questionnaires to 86 respondents. The results of the analysis showed a regression equation Y = 2.422 + 0.655X₁ + 0.251X₂, which indicates that income and education have a positive effect on household consumption. The results of the t-test showed that income had a significant effect on household consumption with a significance value of 0.000 <0.05 and a calculated t of 5.557 > 1.988. Education also had a significant effect with a significance value of 0.028 <0.05 and a calculated t of 2.236 > 1.988. The F-test showed a significance value of 0.000 <0.05 and a calculated F of 75.163 > 3.10, so that income and education simultaneously had an effect on the consumption of poor households. The coefficient of determination (R²) value of 0.644 shows that 64.4% of the variation in household consumption can be explained by income and education..